Penerapan Model Pembelajaran Blended Learning dalam Meningkatkan Hasil Belajar Siswa pada Materi Teks Deskriptif - Ruhendrawati (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2022)
The low student learning outcomes inspired this study. The purpose of this research is to find out the application of blended learning models and to improve student learning outcomes in descriptive text material in MIPA 4 Madrasah Aliyah Negeri 1 Ciamis through the application of these models. The method used in this research is classroom action research with the stages of planning, implementing, observing, and reflecting. The results of the study showed that in the first and second cycles of learning after applying the blended learning model, learning increased significantly. This can be seen from the test results, which have increased. The average score in the pre-cycle was 78.63, increased to 83.43 in cycle I, and in cycle II, to 90.67 from an ideal score of 100. After obtaining the highest score of 100 and the lowest score of 84, which is above the KKM score, the research stopped in cycle II.